Pengaruh Model Pembelajaran Discovery Berbantuan Aplikasi Photomath Terhadap Self Efficacy Matematis Siswa MA - Najwah Rokan; Israq Maharani; Ulfa Annisa Lubis (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This study aims to find out whether there is an influence of the Discovery learning model assisted by the Photomath application on the Self Efficacy of Mathematics for students in class X MA. The research was conducted at MAS Al-Washliyah Johor Gedung Medan, carried out in class X in the even semester of the 2023/2024 school year using a quasi-experimental method with a pretest-posttest non-equivalent control group design. The population in this study is class X which totals 76 students. The sample in this study was taken by Simple Random Sampling. Where class X-A with a total of 38 students is an experimental class and class X-B with a total of 38 students is a control class. Data collection techniques use questionnaires (before and after). Data analysis techniques are normality test, homogeneity test and Independent Sample t-Test. Based on the research results, it can be concluded that there is an influence of the Discovery learning model assisted by the Photomath application on the Mathematical Self Efficacy of class p<0.05 then is accepted and  is rejected. And based on the calculation results with df = 76 – 2 and a significance level of 0.025, it is found that ±  is 1.995 and  is 6.313. Because  >, which is 6.313 > 1.995, then  is accepted and  is rejected. This can also be seen and proven from the average Self Efficacy questionnaire results of students who used the Discovery learning model assisted by the Photomath application, namely 77,08 (before) and 90,08 (after) while students who used Scientific learning assisted by the Photomath application were 78,39 (before) and 79,63 (after) students who used the Photomath-assisted Discovery learning model had a higher average score of the questionnaire data after treatment than students who used Photomath-assisted Scientific learning.